subject
Mathematics, 24.07.2019 20:00 dondre54

Can you turn these inequalities into y=mx+b form? y> 3x-6 4x-y< 7

ansver
Answers: 1

Another question on Mathematics

question
Mathematics, 21.06.2019 17:30
Two customers went to a post office. first customer paid $12 for 14 and 5 envelopes the second paid 24.80 for 10 postcards and 15 envelopes. what is cost of each envelope?
Answers: 1
question
Mathematics, 21.06.2019 22:30
Which of the functions below could have created this graph?
Answers: 1
question
Mathematics, 21.06.2019 23:00
Someone answer this asap for the function f(x) and g(x) are both quadratic functions. f(x) = x² + 2x + 5 g(x) = x² + 2x - 1 which statement best describes the graph of g(x) compared to the graph of f(x)? a. the graph of g(x) is the graph of f(x) shifted down 1 units. b. the graph of g(x) is the graph of f(x) shifted down 6 units. c. the graph of g(x) is the graph of f(x) shifted to the right 1 unit. d. the graph of g(x) is the graph of f(x) shifted tothe right 6 units.
Answers: 3
question
Mathematics, 22.06.2019 01:00
Arrange the steps to solve this system of linear equations in the correct sequence. x + y = -2 2x – 3y = -9 tiles subtract 3x + 3y = -6 (obtained in step 1) from 2x – 3y = -9 (given) to solve for x. substitute the value of x in the first equation (x + y = -2) to get y = 1. the solution for the system of equations is (-3, 1). x = -15 the solution for the system of equations is (-15, 13). add 3x + 3y = -6 (obtained in step 1) to 2x – 3y = -9 (given), and solve for x. x = -3 substitute the value of x in the first equation (x + y = -2) to get y = 13. multiply the first equation by 3: 3(x + y) = 3(-2) 3x + 3y = -6.
Answers: 1
You know the right answer?
Can you turn these inequalities into y=mx+b form? y> 3x-6 4x-y< 7...
Questions
question
Mathematics, 02.04.2020 12:55
question
Mathematics, 02.04.2020 12:56
Questions on the website: 13722363